Pengaruh Gaya Kepemimpinan Dan Kompetensi Pegawai Terhadap Produktivitas Kerja Pada PT Pos Indonesia Di Kota Batam - Vendi Vermanto; Wasiman Wasiman; Yvonne Wangdra (LPPM Universitas Putera Batam, 2023)
Style of leadership is the norm of behavior used by a person when the person is trying to influence the behavior of others as he sees. The term competence lies in part in every human being and forever exist in a person's personality can predict the behavior and performance broadly in all situations and work tasks or jobs task. Meanwhile, pengerak Increased productivity is a motor of economic progress and benefit the company or organization. Productivity is also important to increase wages and individual acceptance. A country that is unable to increase its productivity will decline in the standard of life. Methods: Total population in this study is 564 people and the amount of sample in this study is 234 people, with the Data Collection Techniques questionnaire, sampling technique stratified Sampling.Analisis research using the technique used in this research is multiple linear regression analysis that has a purpose to determine the magnitude of the regression coefficients which will show the level of influence of independent variables on the dependent variable. T test results showed that leadership style variable (X1) significantly affects the Work Productivity (Y) and Employee Competency variables (X2) significantly affects the Work Productivity (Y). F-test results showed that the Leadership Style (X1) and Employee Competence (X2) effect simultaneously on Work Productivity (Y) at PT Pos Indonesia in Batam.